Transformative impact of sport on society: gender equality, values and social well-being - Morales Rivera, Meylin Denisse (Revista Multi-Ensayos, 2025)
The practice of sports is an activity that in itself promotes values that influence society, such as responsibility, honesty, empathy, solidarity, equity, equality, and companionship. In addition, practicing it provides both physical and psychological benefits, important in social and cultural integration for a healthy coexistence. Therefore, this paper is based on the reflection about the advantages of practicing a certain sport, since it has a significant impact in today’s societies and the most important thing is that it is valued as a recreational activity, but also as a fundamental element in the acquisition of values that allow harmonizing social relations. The author, from her experience as a teacher, sports instructor and former high performance soccer athlete, shares her point of view on how the practice of sports influences and impacts the formation of values and the daily life of those who practice a sport.